Spatial and temporal variation of phytoplankton in a tropical eutrophic river - L. M. Santana; M. E. B. Moraes; D. M. L. Silva; C. Ferragut (Brazilian Journal of Biology)
Abstract This study aims to evaluate the environmental factors determining of the changes in phytoplankton structure in spatial (upper, middle and lower course) and seasonal (dry and rainy period) scales in a eutrophic river (Almada River, northeastern Brazil). In the study period, total accumulated rainfall was below of the historic average, resulting in flow reduction, mainly in rainy period. High orthophosphate concentration was found at the sampling sites. Phytoplankton chlorophyll a increased from upstream to downstream. Geitlerinema splendidum (S1) and Chlamydomonas sp. (X2) were the most abundant species in the upper course and several species of diatoms (D), Euglenophyceae (W1, W2) and Chlorophyceae (X1) in the middle and lower course. The functional groups were found to be characteristic of lotic ecosystem, shallow, with low light availability, rich in organic matter and eutrophic environments. We conclude that phytoplankton community structure was sensitive to change of the river flow and nutrient availability in spatial and seasonal scale in a tropical river.